Lithium secondary battery with improved safety
By uniformly distributing inorganic solid electrolyte and gel electrolyte in the positive electrode mixture layer of lithium secondary batteries, the problems of ignition and insufficient performance of lithium secondary batteries at high temperatures are solved, and safety and performance are improved.
Patent Information
- Application Number
- CN202480020308.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-12-12
- Filing Date
- 2024-12-17
- Publication Date
- 2025-11-11
AI Technical Summary
Existing lithium secondary batteries are prone to catching fire due to short circuits between the positive and negative electrodes in high-temperature environments. Furthermore, all-solid-state batteries cannot compare with liquid electrolytes in terms of performance, and suffer from safety, output, and capacity deficiencies.
An inorganic solid electrolyte of 0.5% to 2% by weight is uniformly distributed in the positive electrode mixture layer and combined with a gel-type electrolyte, including lithium salts, non-aqueous organic solvents and polymerizable unsaturated functional groups, to form a surface covering 50% to 90% of the positive electrode active material. Oxide solid electrolytes with NASICON structure, such as lithium aluminum titanium phosphate (LATP), are used.
It effectively delays battery ignition, reduces the explosive force, improves safety, and maintains high battery output and capacity performance.
Smart Images

Figure CN120937165A_ABST
Abstract
Description
Technical Field
[0001] Cross-references to related applications
[0002] This application claims priority and benefit to Korean Patent Application No. 10-2023-0187350, filed with the Korean Intellectual Property Office on December 20, 2023, and Korean Patent Application No. 10-2024-0184498, filed with the Korean Intellectual Property Office on December 12, 2024, the disclosure of which is incorporated herein by reference in its entirety.
[0003] This disclosure relates to lithium secondary batteries with improved safety, and more particularly, to lithium secondary batteries that contain not only an inorganic solid electrolyte in the positive electrode but also a gel electrolyte. Background Technology
[0004] Recently, as the application of lithium secondary batteries has rapidly expanded to power storage supply for large-area devices (such as automobiles and power storage devices) and power supply for electronic devices (such as electrical devices, electronic devices, communication devices and computer devices), the demand for high-capacity, high-output and high-stability lithium secondary batteries has been increasing.
[0005] Typically, a lithium-ion secondary battery includes a positive electrode, a negative electrode, a separator between the positive and negative electrodes, an electrolyte, and an organic solvent. The positive electrode, due to its unstable structure during charging, may generate oxygen, posing a high risk of fire. Therefore, methods to improve the stability of lithium-ion secondary batteries are being researched and developed.
[0006] Separators are used to ensure electrical insulation between the positive and negative electrodes and are typically thin films made of polyolefins. However, in the case of polyolefin-based separators, they may easily shrink at high temperatures and fail to provide insulation between the positive and negative electrodes. When electrical insulation between the positive and negative electrodes becomes impossible, a short circuit occurs, which can react with oxygen generated at the unstable positive electrode and ignite. That is, if a short circuit occurs in a lithium-ion battery under charge at high temperatures, there is a risk of the lithium-ion battery catching fire.
[0007] Therefore, in order to ensure the safety of lithium secondary batteries, whose application areas are expanding, all-solid-state batteries using solid electrolytes are being extensively researched. However, to date, they are known to be unable to exhibit the same output, capacity, and lifespan performance as lithium-ion batteries using liquid electrolytes, and thus are mostly far behind the commercialization level.
[0008] Therefore, the biggest challenge in the industry is ultimately to achieve batteries with improved safety that will not ignite even at considerably high temperatures. However, in lithium-ion batteries using liquid electrolytes, it is difficult to prevent fires caused by the evaporation of the liquid electrolyte and the generation of oxygen at the positive electrode at high temperatures. Therefore, research is actively underway to reduce the explosive force of batteries and ensure that users have sufficient time to evacuate. Summary of the Invention
[0009] Technical issues
[0010] Therefore, one object of this disclosure is to provide a lithium secondary battery that can delay the ignition of the secondary battery and reduce the explosive force, thereby improving the safety of the secondary battery.
[0011] Technical solution
[0012] According to one embodiment of this disclosure, a lithium secondary battery is provided, comprising:
[0013] The positive electrode, wherein a layer of positive electrode mixture comprising positive electrode active material and inorganic solid electrolyte is formed on one or both sides of the positive electrode current collector.
[0014] The negative electrode, wherein a layer of negative electrode mixture containing negative electrode active material is formed on one or both sides of the negative electrode current collector.
[0015] A separator inserted between the positive and negative terminals, and
[0016] Gel electrolytes,
[0017] The inorganic solid electrolyte is included in an amount of 0.5% to 2% by weight based on the total weight of the positive electrode mixture layer, and is uniformly distributed within the positive electrode mixture layer.
[0018] Here, when the cathode mixture layer is divided into two halves based on the thickness direction, the inorganic solid electrolyte may be included in the upper layer in an amount of 40% to 60% by weight and in the lower layer in an amount of 40% to 60% by weight, based on the total weight of the inorganic solid electrolyte. More specifically, when the upper and lower layers are each divided into two halves based on the thickness direction, the inorganic solid electrolyte may be included in each layer in an amount of 20% to 30% by weight, based on the total weight of the inorganic solid electrolyte.
[0019] Furthermore, since the inorganic solid electrolyte is generally uniformly distributed, 50% to 90% of the total surface area of the positive electrode active material can be covered by the inorganic solid electrolyte.
[0020] In this case, the inorganic solid electrolyte can be an oxide-based solid electrolyte having a NASICON structure, and more specifically, it can be an oxide-based solid electrolyte represented by the following chemical formula 1.
[0021] [Chemical Formula 1]
[0022] Li 1+x M' 2-x M x (PO4)3
[0023] In chemical formula 1,
[0024] 0 <x<2,
[0025] M' is selected from at least one of Ti, Zr, Ge, Sn and Hf, and M is selected from at least one of Cr, Al, Mg, Ga, Sc, Y, In and La.
[0026] More specifically, the oxide-based solid electrolyte can be a lithium aluminum titanium phosphate (LATP) compound in which M' is Ti and M is Al.
[0027] The loading capacity of the positive electrode mixture layer can be 400 mg / 25 cm. 2 Up to 600mg / 25cm 2 .
[0028] Simultaneously, lithium secondary batteries may include gel-type electrolytes, and the gel-type electrolytes include: i) lithium salts, ii) non-aqueous organic solvents, and
[0029] iii) At least one polymerizable compound selected from polymerizable monomers, oligomers, and copolymers having polymerizable unsaturated functional groups.
[0030] At least some of the polymerizable unsaturated functional groups may be cured.
[0031] In this case, the polymerizable unsaturated functional group can be at least one selected from vinyl, epoxy, allyl, and (meth)acrylic groups.
[0032] Non-aqueous organic solvents can be carbonate-based organic solvents.
[0033] In addition, the gel electrolyte may also contain a polymerization initiator, which may be a photoinitiator or a thermal initiator. Based on 100 parts by weight of the polymerizable compound, the polymerization initiator may be included in an amount from 0.01 parts by weight to 20 parts by weight.
[0034] In addition, the gel electrolyte may also contain functional additives, and the functional additives may be selected from at least one of the following: sulfonolactone-based compounds, sulfite / ester-based compounds, sulfone-based compounds, sulfate / ester-based compounds, halogen-substituted carbonate-based compounds, nitrile-based compounds, cyclic carbonate-based compounds, phosphate / ester-based compounds, borate / ester-based compounds, and lithium salt-based compounds. Attached Figure Description
[0035] Figure 1 The image shown is a SEM-EDS image of Experiment 1 according to Example 1.
[0036] Figure 2 The image is a SEM-EDS image of Experiment 1 based on Comparative Example 3.
[0037] Figure 3 A graph showing the results of Experimental Example 2 according to Example 1.
[0038] Figure 4 A graph showing the results of Experimental Example 2 according to Example 2.
[0039] Figure 5 A graph showing the results of Experimental Example 2 according to Example 3.
[0040] Figure 6 A graph showing the results of Experimental Example 2 based on Comparative Example 1.
[0041] Figure 7 A graph showing the results of Experimental Example 2 based on Comparative Example 2.
[0042] Figure 8 A graph showing the results of Experimental Example 2 based on Comparative Example 3.
[0043] Figure 9 The capacity retention diagram is based on Experiment 3. Detailed Implementation
[0044] In the following description and claims, the terms or words used should not be construed as limited to their ordinary or dictionary meanings, and this disclosure should be interpreted with meanings and concepts consistent with the technical concept of this disclosure, based on the principle that the inventor can appropriately define the concepts of terms in order to best describe his own invention.
[0045] Unless otherwise defined, all terms used herein (including technical and scientific terms) are to be understood in the sense that would be normally understood by one of ordinary skill in the art to which this disclosure pertains. Furthermore, unless specifically and explicitly defined, terms as defined in commonly used dictionaries should not be interpreted ideally or excessively.
[0046] The terminology used herein is provided to describe embodiments and not to limit the concept of the invention. In this specification, the singular forms include the plural forms unless the context clearly indicates otherwise. The terms “comprising” and / or “including” as used herein do not exclude the presence or addition of one or more elements other than those mentioned.
[0047] Throughout this description, unless otherwise defined, when a part “includes / contains” a component, it does not mean that the part excludes other components, but rather that the part may also include / contain other components.
[0048] One embodiment of the lithium secondary battery according to this disclosure includes:
[0049] The positive electrode, wherein a layer of positive electrode mixture comprising positive electrode active material and inorganic solid electrolyte is formed on one or both sides of the positive electrode current collector.
[0050] The negative electrode, wherein a layer of negative electrode mixture containing negative electrode active material is formed on one or both sides of the negative electrode current collector.
[0051] A separator inserted between the positive and negative terminals, and
[0052] Gel electrolytes,
[0053] The inorganic solid electrolyte is included in an amount of 0.5% to 2% by weight based on the total weight of the positive electrode mixture layer, and is uniformly distributed within the positive electrode mixture layer.
[0054] positive electrode
[0055] The positive electrode has a structure in which a layer of positive electrode mixture containing positive electrode active material and inorganic solid electrolyte is formed on one or both sides of the positive electrode current collector.
[0056] Here, the positive electrode mixture layer can be formed by applying a positive electrode slurry containing a positive electrode active material and an inorganic solid electrolyte to a positive electrode current collector, followed by drying and rolling. In this case, in addition to the materials mentioned above, the positive electrode slurry may also contain electrode materials such as conductive materials and binders.
[0057] There are no particular restrictions on the positive electrode current collector, as long as it is conductive and will not cause any chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, sintered carbon, or aluminum or stainless steel with a surface treated with carbon, nickel, titanium, silver, etc. can be used as the current collector.
[0058] The positive electrode current collector 121 may have a thickness of 3 μm to 500 μm and may have fine protrusions and depressions formed on its surface to enhance the adhesion to the positive electrode active material layer. For example, the positive electrode current collector may be used in various forms such as films, sheets, foils, meshes, porous bodies, foams, and non-woven fabric structures.
[0059] The positive electrode active material is a compound capable of reversibly intercalating and deintercalating lithium, and the positive electrode active material may specifically include lithium metal oxides containing lithium and at least one metal such as cobalt, manganese, nickel, or aluminum. More specifically, the lithium metal oxides may include lithium-manganese-based oxides (e.g., LiMnO2, LiMn2O4, etc.), lithium-cobalt-based oxides (e.g., LiCoO2, etc.), lithium-nickel-based oxides (e.g., LiNiO2, etc.), lithium-nickel-manganese-based oxides (e.g., LiNi 1- Y Mn Y O2 (where 0 < Y < 1), LiMn 2-Z Ni Z O4 (where 0 < Z < 2), etc.), lithium-nickel-cobalt-based oxides (e.g., LiNi 1- Y1 Co Y1 O2 (where, 0 < Y1 < 1), etc.), lithium-manganese-cobalt-based oxides (e.g., LiCo 1-Y2 Mn Y2 O2 (where, 0 < Y2 < 1), LiMn 2-Z1 Co Z1 O4 (where, 0 < Z1 < 2), etc.), lithium-nickel-manganese-cobalt-based oxides (e.g., Li(Ni p Co q Mn r )O2 (where, 0 < p < 1, 0 < q < 1, 0 < r < 1, p + q + r = 1) or Li(Ni p1 Co q1 Mn r1 )O4 (where, 0 < p1 < 2, 0 < q1 < 2, 0 < r1 < 2, p1 + q1 + r1 = 2), etc.), or lithium-nickel-cobalt-transition metal (M) oxides (e.g., Li(Ni p2 Co q2 Mn r2 M s2 )O2 (where M is selected from Al, Fe, V, Cr, Ti, Ta, Mg, and Mo, and p2, q2, r2, and s2 are the atomic fractions of the respective elements, where 0 < p2 < 1, 0 < q2 < 1, 0 < r2 < 1, 0 < s2 < 1, p2 + q2 + r2 + s2 = 1), etc.), lithium iron phosphate (e.g., Li 1+a Fe1-x M x (PO 4-b )X b (where M is selected from at least one of Al, Mg and Ti, X is selected from at least one of F, S and N, and -0.5≤a≤0.5, 0≤x≤0.5, 0≤b≤0.1), and may include any one of them or a mixture of two or more of them.
[0060] Among these materials, lithium metal oxides, in terms of improving battery capacity characteristics and stability, can include LiCoO2, LiMnO2, LiNiO2, and lithium nickel manganese cobalt oxides (e.g., Li(Ni)O2). 1 / 3 Mn 1 / 3 Co 1 / 3 O2, Li(Ni) 0.6 Mn 0.2 Co 0.2 O2, Li(Ni) 0.5 Mn 0.3 Co 0.2 O2, Li(Ni) 0.7 Mn 0.15 Co 0.15 )O2 and Li(Ni 0.8 Mn 0.1 Co 0.1 O2, etc.), lithium nickel cobalt aluminum oxides (e.g., Li(Ni) 0.8 Co 0.15 Al 0.05 (e.g., O2), or lithium nickel manganese cobalt aluminum oxides (e.g., Li(Ni) 0.86 Co 0.05 Mn 0.07 Al 0.02 Lithium iron phosphate (e.g., LiFePO4), etc., and either or a mixture of both or more thereof may be used.
[0061] Based on the total weight of the positive electrode mixture layer, the positive electrode active material may be included in an amount of 60% to 98% by weight, preferably 80% to 98% by weight, and more preferably 90% to 98% by weight.
[0062] Inorganic solid electrolytes may include at least one lithium metal oxide or lithium metal phosphate selected from NASICON-type solid electrolytes, LISICON-type solid electrolytes, garnet-type solid electrolytes, perovskite-type solid electrolytes, and LiPON-type solid electrolytes. More specific examples may include compounds selected from at least one of the following: LAGP (lithium aluminum germanium phosphate), LLZO (lithium lanthanum zirconium oxide), LATP (lithium aluminum titanium phosphate), LLZTO (lithium lanthanum zirconium tantalum oxide), LLTO (lithium lanthanum titanium oxide), LSTP (lithium silicon titanium phosphate), and LGPO (lithium germanium phosphate).
[0063] More specifically, the inorganic solid electrolyte can be a NASICON-type solid electrolyte as in the examples above, and can be an oxide-based solid electrolyte with a NASICON-type structure, and more specifically, can be represented by the following chemical formula 1.
[0064] [Chemical Formula 1]
[0065] Li 1+x M' 2-x M x (PO4)3
[0066] In chemical formula 1,
[0067] 0 <x<2,
[0068] M' is selected from at least one of Ti, Zr, Ge, Sn and Hf, and M is selected from at least one of Cr, Al, Mg, Ga, Sc, Y, In and La.
[0069] More specifically, the oxide-based solid electrolyte can be a lithium aluminum titanium phosphate (LATP) compound in which M' is Ti and M is Al.
[0070] Based on the total weight of the cathode mixture layer, the inorganic solid electrolyte may be included in an amount of 0.5% to 2% by weight, and more specifically 0.5% to 1% by weight.
[0071] If the content is too low and outside the above range, it is difficult to achieve the expected reduction in explosive power as disclosed in this disclosure. If the content is too high, there is a problem of increased resistance in the lithium secondary battery, which is not preferred.
[0072] In addition, inorganic solid electrolytes can be uniformly distributed within the positive electrode mixture layer.
[0073] Here, "uniform distribution" means that when the cathode mixture layer is divided into two or more layers based on the thickness direction, the difference in the content of inorganic solid electrolyte contained in the two or more layers does not exceed 20% by weight when the total weight of the inorganic solid electrolyte is 100% by weight.
[0074] In other words, this means that when the cathode mixture layer is divided into two layers based on the thickness direction, and when the total inorganic solid electrolyte is 100% by weight, the content of inorganic solid electrolyte in each of the upper and lower layers does not deviate from the ratio of 40:60 to 60:40.
[0075] Therefore, when the cathode mixture layer is divided into two halves based on the thickness direction, the inorganic solid electrolyte can be included in the upper layer in an amount of 40% to 60% by weight and in the lower layer in an amount of 40% to 60% by weight, based on the total weight of the inorganic solid electrolyte.
[0076] More specifically, when the upper and lower layers are each divided into two halves based on the thickness direction, the inorganic solid electrolyte can be included in each layer in an amount of 20% to 30% by weight, based on the total weight of the inorganic solid electrolyte.
[0077] Here, dividing the cathode mixture layer into two halves based on the thickness direction does not mean that the cathode mixture layer is formed in two or more layers, but rather that the formed cathode mixture layer is divided into upper and lower layers based on the thickness direction for analysis.
[0078] Furthermore, since the inorganic solid electrolyte is uniformly distributed in the positive electrode mixture layer in this way, the surface of the positive electrode active material can be covered by 50% or more of the total surface area of the positive electrode active material, specifically 50% to 90%, more specifically 50% to 80%, and most specifically 60% to 80%.
[0079] If less than 50% of the surface of the positive electrode active material is covered outside the above range, the safety intended by this disclosure cannot be adequately ensured, and this is not preferred.
[0080] Furthermore, the average diameter (D50) of the inorganic solid electrolyte particles can be from 50 nanometers to 10 micrometers, specifically from 50 nanometers to 5 micrometers, and more specifically from 50 nanometers to 1 micrometer.
[0081] If the average diameter is too small and falls outside the above range, particle aggregation may occur due to reduced dispersibility. Conversely, if the average diameter is too large, the pores become too large due to the inorganic solid electrolyte, which is not preferable in terms of resistance. That is, when the average diameter meets the above range, lithium-ion conductivity can increase, thereby reducing resistance and exhibiting improved secondary battery performance.
[0082] As used herein, the average diameter D50 refers to the particle diameter at which the cumulative volume of the particles reaches 50% in the particle size distribution curve. D50 can be measured, for example, using laser diffraction. Laser diffraction can typically measure particle diameters in the submicron to millimeter range and can yield results with high reproducibility and high resolution.
[0083] Conductive materials are components used to further improve the conductivity of the positive electrode active material. There are no particular limitations on such conductive materials, as long as they are conductive without causing any chemical changes in the battery. Examples of conductive materials that can be used include: carbon powders such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lampblack, or thermally cracked black; graphite powders such as natural graphite, artificial graphite, or graphite with a well-formed crystal structure; conductive fibers such as carbon fibers or metal fibers; fluorinated carbon powders; conductive powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; or conductive materials such as polyphenylene derivatives.
[0084] Based on the total weight of the positive electrode mixture layer, the conductive material may be included in an amount of 0.1 wt% to 20 wt%, specifically 0.5 wt% to 10 wt%, and more specifically 0.5 wt% to 5 wt%.
[0085] Binders are components that facilitate the bonding between conductive materials, positive electrode active materials, and positive electrode current collectors. Examples of binders can include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polyethylene, polypropylene, ethylene propylene diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber, and various copolymers thereof.
[0086] Typically, the binder may be included in an amount of 0.5% to 20% by weight, specifically 0.5% to 10% by weight, and more specifically 0.5% to 5% by weight, based on the total weight of the cathode mixture layer.
[0087] In addition, other additives may include, for example, fillers as components used to suppress expansion. There are no particular limitations on fillers, as long as they can suppress electrode expansion without causing any chemical changes in the battery, and examples may include: olefinic polymers, such as polyethylene and polypropylene; and fibrous materials, such as glass fiber and carbon fiber.
[0088] Meanwhile, the loading of the positive electrode mixture layer can be 400 mg / 25 cm⁻¹. 2 Up to 600mg / 25cm 2 Specifically, 450mg / 25cm 2Up to 600mg / 25cm 2 And more specifically 450mg / 25cm 2 Up to 550mg / 25cm 2 .
[0089] That is, under the present disclosure, even when using a high-load positive electrode, the high safety of the secondary battery can be ensured by the uniform distribution of the inorganic solid electrolyte.
[0090] negative electrode
[0091] The negative electrode has a structure in which a layer of negative electrode mixture is formed on one or both sides of the negative electrode current collector.
[0092] Here, the negative electrode mixture layer can be formed by applying a negative electrode slurry containing a negative electrode active material to a negative electrode current collector, followed by drying and rolling, wherein in addition to the negative electrode active material, the negative electrode slurry may also contain electrode materials such as conductive materials and binders as described above.
[0093] There are no particular limitations on the negative electrode current collector 111, as long as it has high conductivity and does not cause any chemical changes in the battery. Examples of negative electrode current collectors can include copper, stainless steel, aluminum, nickel, titanium, sintered carbon; copper or stainless steel with surfaces treated with carbon, nickel, titanium, silver, etc.; aluminum-cadmium alloys; and so on.
[0094] The thickness of the negative electrode current collector 111 can typically range from 3 μm to 500 μm. Similar to the positive electrode current collector, the negative electrode current collector can have fine protrusions and depressions formed on its surface to enhance the adhesion to the negative electrode active material. For example, the negative electrode current collector can be used in a wide variety of forms such as films, sheets, foils, meshes, porous bodies, foams, and nonwoven fabric structures.
[0095] The negative electrode active material may include at least one of the following: lithium metal, carbon material capable of reversibly inserting / de-inserting lithium ions, metal or alloy of these metals with lithium, metal composite oxide, material capable of doping and de-doping lithium, and transition metal oxide.
[0096] As a carbon material capable of reversibly inserting / deintercalating lithium ions, any carbon material can be used without particular limitation, as long as it is a carbon-based negative electrode active material commonly used in lithium-ion secondary batteries. Representative examples include crystalline carbon, amorphous carbon, or both. Examples of crystalline carbon include graphite such as irregular, planar, flake-like, spherical, or fibrous natural or artificial graphite. Examples of amorphous carbon include soft carbon (low-temperature calcined carbon) or hard carbon, mesophase pitch carbides, calcined coke, etc.
[0097] As the metal or an alloy of these metals with lithium, metals selected from Cu, Ni, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn or alloys of these metals with lithium can be used.
[0098] As the metal composite oxide, at least one selected from the following can be used: PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, Bi2O5, Li x Fe2O3 (where 0 ≤ x ≤ 1), Li x WO2 (where 0 ≤ x ≤ 1), and Sn x Me 1-x Me' y O z (where Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, elements of Group 1, Group 2, and Group 3 of the periodic table, halogens; 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8).
[0099] Materials capable of doping and undoping lithium can include Si, SiO x (0 < x ≤ 2), Si-Y alloy (where Y is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations thereof and is not Si), Sn, SnO2, Sn-Y (where Y is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations thereof and is not Sn), etc., and at least one of these can be mixed with and used with SnO2. The element Y can be selected from Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof.
[0100] Transition metal oxides can include lithium-containing titanium composite oxides (LTO), vanadium oxides, lithium vanadium oxides, etc.
[0101] Based on the total weight of the negative electrode active material layer, the negative electrode active material can be included in an amount of 60% to 99% by weight, preferably 80% to 99% by weight, and more preferably 90% to 98% by weight.
[0102] When using the metal itself without forming a negative electrode mixture layer on the negative electrode, it can be manufactured by physically bonding, rolling, or depositing the metal onto the metal film itself or the negative electrode current collector. As deposition methods, metal electrodeposition or chemical vapor deposition can be used.
[0103] For example, the metal bonded / rolled / deposited on the metal film itself or the negative electrode current collector may include one type of metal selected from lithium (Li), nickel (Ni), tin (Sn), copper (Cu) and indium (In), or an alloy of two types thereof.
[0104] Separator
[0105] The separator can be used without particular restrictions, as long as it is commonly used as a separator in lithium secondary batteries, and those that have low resistance to ion migration in the electrolyte and excellent electrolyte moisture-holding capacity are particularly preferred.
[0106] For example, as a separator, a porous polymer membrane comprising two or more layers of a polyolefin-based polymer (e.g., ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer, and ethylene / methacrylate copolymer) can be used. Alternatively, typical porous nonwoven fabrics, such as nonwoven fabrics made of high-melting-point glass fibers, polyethylene terephthalate fibers, etc., can be used as separators.
[0107] Alternatively, it can be an SRS (Safety Reinforced Separator) separator having a structure in which a coating comprising inorganic particles and adhesive material is formed on one or both sides of a polymer substrate as described above.
[0108] The SRS separator is as described above. Specifically, the polyolefin base of the SRS separator is as described above, and the coating comprises inorganic particles and adhesive materials.
[0109] Here, inorganic particles enable the formation of empty spaces between them, thus acting as spacers that create micropores and maintain physical shape. Since inorganic particles typically retain their physical properties even at temperatures up to 200°C or higher, the resulting organic / inorganic mixture layer exhibits excellent heat resistance.
[0110] There are no particular limitations on the inorganic particles, as long as they are electrochemically stable. That is, there are no particular limitations on the inorganic particles that can be used in this disclosure, as long as they do not undergo oxidation and / or reduction reactions within the operating voltage range of the battery in use. In particular, when inorganic particles with ion transfer capabilities are used, the ionic conductivity within the electrochemical device can be improved and performance enhancement can be promoted, and therefore, inorganic particles with higher ionic conductivity are preferred. Furthermore, when inorganic particles have a high density, there are problems such as increased weight of the secondary battery during manufacturing and difficulties in dispersion during manufacturing. Therefore, if possible, inorganic particles with a lower density are preferred. In addition, inorganic particles with a high dielectric constant can help increase the dissociation of electrolyte salts (e.g., lithium salts) in the liquid electrolyte, thereby enhancing the ionic conductivity of the electrolyte. Finally, inorganic particles with thermal conductivity have excellent endothermic capabilities, and therefore, heat localization to form heating points, thereby suppressing phenomena leading to thermal runaway, which is more preferable.
[0111] For the reasons stated above, inorganic particles may preferably be selected from at least one of the following types: (a) inorganic particles with a high dielectric constant of 1 or greater, 5 or greater, preferably 10 or greater; (b) inorganic particles with piezoelectricity; (c) thermally conductive inorganic particles; and (d) inorganic particles with the ability to transport lithium ions.
[0112] Piezoelectric inorganic particles are materials that are non-conductive under normal pressure but exhibit conductive properties due to changes in their internal structure when pressure is applied. They are materials that not only possess a high dielectric constant, such as 100 or greater, but also have the ability to generate a potential difference between two surfaces when one surface is positively charged and the opposite surface is negatively charged, in the case of piezoelectric materials being stretched or compressed under applied pressure.
[0113] Examples of piezoelectric inorganic particles include BaTiO3, Pb(Zr,Ti)O3(PZT), and Pb 1-x La x Zr 1- y Ti y O3(PLZT), PB(Mg3Nb) 2 / 3 Hafnium oxide (HfO2) or mixtures thereof, but not limited to these.
[0114] "Inorganic particles having the ability to transport lithium ions" refers to inorganic particles that contain lithium atoms and have the ability to move lithium ions without storing lithium. Since the inorganic particles having the ability to transport lithium ions can transfer and migrate lithium ions due to certain defects present within the particle structure, it is possible to prevent a decrease in lithium mobility and thus prevent a decrease in battery capacity.
[0115] Examples of inorganic particles having the ability to transport lithium ions can be lithium phosphate (Li3PO4); lithium titanium phosphate (Li x Ti y (PO4)3, 0 < x < 2, 0 < y < 3); lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, 0 < x < 2, 0 < y < 1, 0 < z < 3); glass based on (LiAlTiP) x O y (0 < x < 4, 0 < y < 13) such as 14Li2O - 9Al2O3 - 38TiO2 - 39P2O5; lithium lanthanum titanate (Li x La y TiO3, 0 < x < 2, 0 < y < 3); lithium germanium thiophosphate (Li x Ge y P z S w , 0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5) such as Li 3.25 Ge 0.25 P 0.75 S4; lithium nitride (Li x N y , 0 < x < 4, 0 < y < 2) such as Li3N; glass based on SiS2 (Li x Si y S z , 0 < x < 3, 0 < y < 2, 0 < z < 4) such as Li3PO4 - Li2S - SiS2; glass based on P2S5 (Li x P y S z , 0 < x < 3, 0 < y < 3, 0 < z < 7) such as LiI - Li2S - P2S5; or a mixture thereof, but not limited thereto.
[0116] In addition, examples of inorganic particles having a dielectric constant of 1 or greater can be SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, Y2O3, Al2O3, TiO2, SiC or a mixture thereof, but not limited thereto.
[0117] Thermally conductive inorganic particles are materials that provide low thermal resistance but not electrical conductivity and thus have insulating properties, and examples of such particles may be selected from at least one of aluminum nitride (AlN), boron nitride (BN), aluminum oxide (Al2O3), silicon carbide (SiC) and beryllium oxide (BeO), but are not limited thereto.
[0118] When the above-mentioned high dielectric constant inorganic particles, piezoelectric inorganic particles, thermally conductive inorganic particles, and inorganic particles capable of transporting lithium ions are used in combination, the synergistic effect of these particles can be doubled.
[0119] There is no limitation on the size of the inorganic particles, but to ensure appropriate porosity between the particles, a size in the range of 0.001 μm to 10 μm is preferred, if possible. When the size is less than 0.001 μm, dispersibility deteriorates and physical properties become difficult to adjust. When the size is greater than 10 μm, the thickness increases and mechanical properties deteriorate. Furthermore, due to the excessively large pore size, the coating cannot function effectively, and the possibility of internal short circuits during battery charging and discharging increases.
[0120] There is no particular limitation on the content of inorganic particles, but it is preferably in the range of 1% to 99% by weight, and especially 10% to 95% by weight, based on 100% by weight of the mixture of inorganic particles and binder material. If the content of inorganic particles is less than 1% by weight, the content of binder material may be too high, resulting in a reduction in pore size and porosity due to the reduced space between inorganic particles, thereby reducing the mobility of lithium ions. On the other hand, when the content exceeds 99% by weight, the content of binder material is too low, so the adhesion between inorganic materials becomes weak, and therefore the mechanical properties of the coating deteriorate.
[0121] Meanwhile, there are no restrictions on the adhesive material, as long as it does not cause side reactions with the electrolyte. However, in particular, adhesive materials with the lowest possible glass transition temperature (Tg) can be used, preferably in the range of -200°C to 200°C. This is because it can improve the mechanical properties of the final insulating film.
[0122] Furthermore, adhesive materials do not necessarily have to be ion-conducting, but it is preferable to use polymers that are ion-conducting.
[0123] Therefore, if possible, the adhesive material preferably has a high dielectric constant. In fact, since the degree of dissociation of salts in an electrolyte depends on the dielectric constant of the electrolyte solvent, the higher the dielectric constant of the polymer, the greater the degree of salt dissociation in the electrolyte can be. The dielectric constant of the polymer can be 1 or greater, specifically in the range of 1.0 to 100 (measurement frequency = 1 kHz), and particularly preferably 10 or greater.
[0124] In addition to the aforementioned functions, the binder material can also exhibit high electrode impregnation (swelling degree) through gelation when immersed in a liquid electrolyte. In fact, when the binder material has excellent electrode impregnation, the electrolyte injected after battery assembly can permeate into the polymer, and the polymer containing the absorbed electrolyte possesses electrolyte ion conductivity. Therefore, if possible, a solubility parameter of 15 MPa is preferred. 1 / 2 up to 45MPa 1 / 2 The polymer, and more preferably 15 MPa 1 / 2 Up to 25MPa 1 / 2 and 30MPa 1 / 2 up to 45MPa 1 / 2 The range. When the solubility parameter is less than 15 MPa. 1 / 2 and greater than 45MPa 1 / 2 At that time, it becomes difficult to use it for the typical liquid electrolyte impregnation (swelling) of batteries.
[0125] Examples of adhesive materials include those selected from at least one of the following: polyvinylidene fluoride-copoly-hexafluoropropylene, polyvinylidene fluoride-copoly-trichloroethylene, polymethyl methacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, polyethylene-copoly-vinyl acetate, polyimide, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, and polyvinyl alcohol.
[0126] The total thickness of the separator can range from 5 micrometers to 20 micrometers, specifically 5 micrometers to 15 micrometers, and more specifically 6 micrometers to 13 micrometers. If the separator thickness meets these ranges, short circuits between the positive and negative electrodes can be effectively prevented, while minimizing the resistance of the lithium-ion battery. Therefore, the energy density of the lithium-ion battery can be prevented from decreasing, and its lifespan characteristics can be improved.
[0127] Gel electrolyte
[0128] Gel electrolytes contain: i) lithium salts, ii) non-aqueous organic solvents, and
[0129] iii) At least one polymerizable compound selected from polymerizable monomers, oligomers, and copolymers having polymerizable unsaturated functional groups.
[0130] At least some of the polymerizable unsaturated functional groups may be cured.
[0131] Here, lithium salts are used as a medium for transferring ions within a lithium secondary battery. For example, lithium salts may contain Li. +It is a cation, and may contain at least one of the following as an anion: F - Cl - ,Br - I - NO3 - N(CN)2 - BF4 - ClO4 - B 10 Cl 10 - AlCl4 - AlO2 - PF6 - CF3SO3 - CH3CO2 - CF3CO2 - AsF6 - SbF6 - CH3SO3 - (CF3CF2SO2)2N - (CF3SO2)2N - (FSO2)2N - BF2C2O4 - BC4O8 - PF4C2O4 - PF2C4O8 - (CF3)2PF4 - (CF3)3PF3 - (CF3)4PF2 - (CF3)5PF - (CF3)6P - C4F9SO3 - CF3CF2SO3 - CF3CF2(CF3)2CO - (CF3SO2)2CH - CF3(CF2)7SO3 - and SCN - .
[0132] Specifically, lithium salts may include single substances, or mixtures of two or more of the following: LiCl, LiBr, LiI, LiBF4, LiClO4, LiB 10 Cl 10LiAlCl4, LiAlO2, LiPF6, LiCF3SO3, LiCH3CO2, LiCF3CO2, LiAsF6, LiSbF6, LiCH3SO3, LiFSI (lithium bis(fluorosulfonyl)imide, LiN(SO2F)2), LiBETI (lithium bis(perfluoroethanesulfonyl)imide, LiN(SO2CF2CF3)2) and LiTFSI (lithium bis(trifluoromethanesulfonyl)imide, LiN(SO2CF3)2), but for the sake of excellent stability, LiN(SO2CF3)2 is preferred.
[0133] Apart from these, lithium salts commonly used in the electrolytes of lithium secondary batteries can be used without particular restrictions.
[0134] The concentration of lithium salt can be appropriately varied within the generally available range; however, to achieve the best effect in forming a film to prevent corrosion of the electrode surface, lithium salt can be included in the electrolyte at a concentration of 0.5M to 3M, specifically 1M to 2.5M, and more specifically 1M to 2M. When the concentration of lithium salt meets the above range, the effect of improving the cycle characteristics of lithium secondary batteries during high-temperature storage is sufficient, and the viscosity of the electrolyte is suitable to improve electrolyte impregnation.
[0135] There are no restrictions on non-aqueous organic solvents, as long as they minimize decomposition caused by oxidation reactions, etc., within the voltage range of the charging / discharging process of lithium secondary batteries, and exhibit the desired properties together with additives. For example, carbonate-based organic solvents, ether-based organic solvents, ester-based organic solvents, etc., or mixtures of two or more thereof, can be used alone, and specifically, carbonate-based organic solvents can be used.
[0136] Organic solvents based on carbonates may include at least one selected from organic solvents based on cyclic carbonates and organic solvents based on linear carbonates. Specifically, organic solvents based on cyclic carbonates may include at least one selected from: ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentene carbonate, 2,3-pentene carbonate, vinylene carbonate, ethylene ethylene carbonate, and fluoroethylene carbonate (FEC). Specifically, it may include a mixed solvent of ethylene carbonate having a high dielectric constant and propylene carbonate having a relatively low melting point compared to ethylene carbonate.
[0137] Furthermore, the organic solvent based on linear carbonates is a solvent with low viscosity and low dielectric constant, and may include at least one selected from dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, methyl ethyl carbonate (EMC), methyl propyl carbonate and ethyl propyl carbonate, and more specifically, it may include dimethyl carbonate.
[0138] Ether-based organic solvents may include, but are not limited to, any one of ethylene glycol dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether and ethyl propyl ether, or mixtures of two or more thereof.
[0139] Ester-based organic solvents may include at least one selected from linear ester-based organic solvents and cyclic ester-based organic solvents.
[0140] Specific examples of organic solvents based on linear esters may include, but are not limited to, any one of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate and butyl propionate, or mixtures of two or more thereof.
[0141] Specific examples of organic solvents based on cyclic esters may include, but are not limited to, any one of γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone and ε-caprolactone, or mixtures of two or more thereof.
[0142] In ester-based solvents, cyclic carbonate-based compounds are preferred because they act as highly viscous organic solvents and readily dissociate lithium salts in the electrolyte due to their high dielectric constant. When cyclic carbonate-based compounds are mixed in appropriate ratios with low-viscosity, low-dielectric-constant linear carbonate-based compounds (e.g., dimethyl carbonate and diethyl carbonate), gel-type electrolytes with high conductivity can be prepared, which is even more preferable.
[0143] Meanwhile, polymerizable compounds, including polymerizable monomers, oligomers, or copolymers, are substances having polymerizable unsaturated functional groups, such as compounds having polymerizable unsaturated functional groups selected from vinyl, epoxy, allyl, and (meth)acrylic groups, and which can be converted into gel-type compounds through polymerization or crosslinking. There are no particular limitations on polymerizable compounds, as long as they are commonly used as polymerizable monomers, oligomers, or copolymers for preparing gel-type polymer electrolytes.
[0144] More specifically, non-limiting examples of polymerizable monomers or oligomers include tetraethylene glycol diacrylate, polyethylene glycol diacrylate (molecular weight: 50 to 20,000), 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, trimethylolpropane ethoxylate triacrylate, trimethylolpropane propoxylate triacrylate, bis(trimethylolpropane) tetraacrylate, pentaerythritol tetraacrylate, and pentaerythritol ethoxylate. Tetraacrylates, dipentaerythritol pentaacrylates, dipentaerythritol hexaacrylates, poly(ethylene glycol) diglycidyl ether, 1,5-hexadiene diepoxide, glycerol propoxylated triglycidyl ether, vinylcyclohexene dioxide, 1,2,7,8-diepoxyoctane, 4-vinylcyclohexene dioxide, butyl glycidyl ether, 1,2-cyclohexane dicarboxylic acid diglycidyl ether, ethylene glycol diglycidyl ether, glycerol triglycidyl ether, glycidyl methacrylate, etc. Such compounds can be used alone or in mixtures of two or more thereof.
[0145] In addition, representative examples of copolymers include at least one copolymer selected from the following: allyl 1,1,2,2-tetrafluoroethyl ether (TFE)-(2,2,2-trifluoroethyl acrylate) polymer, TFE-vinyl acetate, TFE-(2-vinyl-1,3-dioxolane) polymer, TFE-vinyl methacrylate polymer, TFE-acrylonitrile polymer, TFE-vinyl acrylate polymer, TFE-copoly-methyl acrylate polymer, TFE-methyl methacrylate (MMA) polymer, and TFE-2,2,2-trifluoroethyl acrylate (FA) polymer.
[0146] Based on the total weight of the gel electrolyte, the polymer formed by curing the above materials can be included in an amount from 0.01% to 10% by weight. When the polymer content is greater than 10% by weight, the amount of polymerizable material increases during the preparation of the gel electrolyte, causing gelation to occur too quickly or form too densely, resulting in the disadvantage of obtaining a gel with high electrical resistance. Conversely, when the content is less than 0.01% by weight, the gelation effect cannot be obtained, which is not preferred.
[0147] Furthermore, the gel electrolyte of this disclosure may also include a polymerization initiator for polymerizing polymerizable unsaturated functional groups, and conventional thermal polymerization initiators or photopolymerization initiators known in the art may be used. For example, the initiator may be thermally decomposed to form free radicals, and react with polymerizable monomers, oligomers, or polymers via free radical polymerization to form a gel electrolyte.
[0148] More specifically, examples of polymerization initiators include: organic peroxides or hydroperoxides, such as benzoyl peroxide, acetyl peroxide, dilauryl peroxide, di-tert-butyl peroxide, tert-butyl peroxide-2-ethylhexanoate, cumyl hydroperoxide, and hydroperoxide; at least one azo compound selected from, but not limited to, 2,2'-azobis(2-cyanobutane), 2,2'-azobis(methylbutyronitrile), 2,2'-azobis(isobutyronitrile) (AIBN), and 2,2'-azobisdimethylpentanonitrile (AMVN).
[0149] In lithium secondary batteries, polymerization initiators decompose by heating (as a non-limiting example, including heating from 30°C to 100°C) or at room temperature (5°C to 30°C) to form free radicals, and polymerizable unsaturated functional groups of polymerizable monomers, oligomers or polymers can react by free radical polymerization to form gel electrolytes.
[0150] Based on 100 parts by weight of the polymerizable compound, the polymerization initiator may be included in an amount of 0.01 parts by weight to 20 parts by weight, particularly 0.01 parts by weight to 1 part by weight.
[0151] When a polymerization initiator is included in the range of 0.01 parts by weight to 20 parts by weight, the gel conversion rate can be improved, thus ensuring the gel-type electrolyte properties and preventing pre-gelation reaction, thereby improving the wettability of the electrolyte to the electrode.
[0152] In addition, gel electrolytes may also contain functional additives, which may be used to prevent the negative electrode from decomposing and collapsing in high-power environments, or to further improve low-temperature high-rate discharge characteristics, high-temperature stability, overcharge prevention, and battery swelling suppression during high-temperature storage.
[0153] Specifically, as a representative example, functional additives may include at least one functional additive selected from the following: sulfonyl lactone-based compounds, sulfite / ester-based compounds, sulfone-based compounds, sulfate / ester-based compounds, halogen-substituted carbonate-based compounds, nitrile-based compounds, cyclic carbonate-based compounds, phosphate / ester-based compounds, borate / ester-based compounds, and lithium salt-based compounds.
[0154] The sulfonyl-based compound may include at least one compound selected from the group consisting of 1,3-propanesulfonyl (PS), 1,4-butanesulfonyl, ethanesulfonyl, 1,3-propenesulfonyl (PRS), 1,4-butenesulfonyl, and 1-methyl-1,3-propenesulfonyl, and may be included in an amount from 0.3% to 5% by weight, and specifically from 1% to 5% by weight, based on the total weight of the gel electrolyte. When the amount of the sulfonyl-based compound in the gel electrolyte exceeds 5% by weight, an excessively thick layer may form on the electrode surface, leading to increased resistance and decreased output. Furthermore, the increased resistance due to excessive additives may degrade output characteristics.
[0155] The sulfite / ester-based compound may include at least one compound selected from the following: ethylene sulfite, methyl ethylene sulfite, ethyl ethylene sulfite, 4,5-dimethyl ethylene sulfite, 4,5-diethyl ethylene sulfite, propylene sulfite, 4,5-dimethyl propylene sulfite, 4,5-diethyl propylene sulfite, 4,6-dimethyl propylene sulfite, 4,6-diethyl propylene sulfite, and 1,3-butanediol sulfite, and may be included in an amount of 3% by weight or less based on the total weight of the gel electrolyte.
[0156] The sulfone-based compounds may include at least one compound selected from divinyl sulfone, dimethyl sulfone, diethyl sulfone, methyl ethyl sulfone, and methyl vinyl sulfone, and may be included in an amount of 3% by weight or less based on the total weight of the gel electrolyte.
[0157] The sulfate / ester-based compound may include ethylene sulfate (Esa), trimethylene sulfate (TMS), or methyltrimethylene sulfate (MTMS), and may be included in an amount of 3% by weight or less based on the total weight of the gel electrolyte.
[0158] Furthermore, halogen-substituted carbonate-based compounds may include fluoroethylene carbonate (FEC) and may be included in an amount of 5% by weight or less, based on the total weight of the gel electrolyte. Where the amount of halogen-substituted carbonate-based compounds in the gel electrolyte exceeds 5% by weight, the battery swelling performance may be reduced.
[0159] In addition, nitrile-based compounds may include at least one compound selected from the following: succinate, adiponitrile (Adn), acetonitrile, propionitrile, butyronitrile, valerate, octanoic acid, heptanoic acid, cyclopentaneformitrile, cyclohexaneformitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, phenylacetonitrile, 2-fluorophenylacetonitrile, and 4-fluorophenylacetonitrile.
[0160] The cyclic carbonate-based compound may include vinylene carbonate (VC) or ethylene ethylene carbonate, and may be included in an amount of 3% by weight or less based on the total weight of the gel electrolyte. If the content of the cyclic carbonate-based compound in the gel electrolyte is greater than 3% by weight, the battery swelling suppression performance may be reduced.
[0161] The phosphate / ester-based compound may include at least one compound selected from the following: lithium difluoro(bis(oxalato)phosphate), lithium difluorophosphate, tetramethyltrimethylsilyl phosphate, trimethylsilyl phosphite, tris(2,2,2-trifluoroethyl) phosphate, and tris(trifluoroethyl) phosphite, and may be included in an amount of 3% by weight or less based on the total weight of the gel electrolyte.
[0162] Compounds based on borates / esters may include lithium oxaloyl difluoroborate, and may be included in an amount of 3% by weight or less based on the total weight of the gel electrolyte.
[0163] The lithium salt-based compound is a compound that differs from the lithium salt contained in the gel electrolyte. The lithium salt-based compound may include at least one compound selected from LiPO2F2, LiODFB, LiBOB (lithium bis(oxalatoborate) (LiB(C2O4)2), and LiBF4), and may be included in an amount of 3% by weight or less based on the total weight of the gel electrolyte.
[0164] Two or more functional additives may be mixed and included in an amount of 20% by weight or less, specifically from 0.1% to 10% by weight, based on the total weight of the gel electrolyte. If the content of the functional additives is greater than 20% by weight, there is a possibility that excessive side reactions may occur in the gel electrolyte during battery charging and discharging. In particular, they may not decompose sufficiently at high temperatures and may exist in the gel electrolyte as unreacted substances or in a precipitated state at room temperature. Therefore, side reactions that reduce the lifespan or resistivity characteristics of the lithium secondary battery may occur.
[0165] In the following description, a lithium secondary battery according to one embodiment of the present disclosure will be shown with reference to examples to demonstrate its improved performance.
[0166] <Example 1>
[0167] Preparation of positive electrode
[0168] A 15-micrometer-thick aluminum (Al) metal film is prepared as the positive electrode current collector. Li(Ni) is used as the positive electrode active material. 0.8 Mn 0.1 Co 0.1 O2, Li as an inorganic solid electrolyte1.4 Al 0.4 Ti 1.6 (PO4)3(LATP), carbon nanotubes as conductive materials, and PVDF as a binder were added to NMP solvent in a weight ratio of 95:1:1:3 and dispersed to prepare a positive electrode slurry. The positive electrode slurry was coated onto one side of an aluminum metal film to a thickness of 60 micrometers, then dried and rolled to prepare the positive electrode (loading: 450 mg / 25 cm). 2 ).
[0169] Preparation of negative electrode
[0170] Next, a 20-micrometer-thick copper (Cu) metal film was prepared as the negative electrode current collector. Graphite (as the negative electrode active material), carbon black (as the conductive material), carboxymethyl cellulose (CMC) (as the thickener), and styrene-butadiene rubber (SBR) (as the binder) were added to water in a weight ratio of 95:1:1.5:2.5 and dispersed to prepare a negative electrode slurry. The negative electrode slurry was coated onto one side of the copper metal film to a thickness of 75 micrometers, then dried and rolled to prepare the negative electrode.
[0171] Preparation of electrode components
[0172] An electrode assembly is fabricated by inserting a polyolefin separator (thickness: 15 micrometers) between the positive and negative electrodes.
[0173] Manufacturing of lithium secondary batteries
[0174] LiPF6 was dissolved in a non-aqueous organic solvent with a composition of ethylene carbonate (EC): methyl ethyl carbonate (EMC) = 30:70 (volume ratio) to a concentration of 1.0 M. Trimethylolpropane triacrylate was added as a polymerizable compound at 4% by weight of the total weight, and azobisisobutyronitrile (AIBN, V59) was added as a polymerization initiator at 0.02% by weight of 100% by weight of the polymerizable compound to prepare a gel polymer electrolyte composition.
[0175] The electrode assembly prepared above was inserted into the battery case, and the gel polymer electrolyte composition prepared above was injected to manufacture a secondary battery. Then, after wetting the battery case with the electrolyte at room temperature for 2 days, the gel polymer electrolyte composition was allowed to stand and polymerize in a room at 60°C for 5 hours to manufacture a lithium secondary battery.
[0176] <Example 2>
[0177] The lithium secondary battery was manufactured in the same manner as in Example 1, except that in the gel polymer electrolyte composition of Example 1, a polymerizable compound was added to 10% by weight of the total weight.
[0178] <Example 3>
[0179] The lithium secondary battery was manufactured in the same manner as in Example 1, except that Li(Ni) was added as the positive electrode active material in a weight ratio of 94:2:1:3 to the positive electrode of Example 1. 0.8 Mn 0.1 Co 0.1 O2, Li as an inorganic solid electrolyte 1.4 Al 0.4 Ti 1.6 (PO4)3(LATP), carbon nanotubes as conductive materials, and PVDF as a binder.
[0180] <Comparative Example 1>
[0181] The lithium secondary battery was manufactured in the same manner as in Example 1, except that in the positive electrode of Example 1, Li(Ni)2, used as the positive electrode active material, was mixed in a weight ratio of 96:1:3. 0.8 Mn 0.1 Co 0.1 O2, carbon nanotubes as conductive materials, and PVDF as binders are injected into a liquid electrolyte solution in which LiPF6 is dissolved at a concentration of 1.0M in a non-aqueous organic solvent with a composition of ethylene carbonate (EC): methyl ethyl carbonate (EMC) = 30:70 (volume ratio), replacing the gel polymer electrolyte composition, and only the impregnation process is performed.
[0182] <Comparative Example 2>
[0183] The lithium secondary battery was manufactured in the same manner as in Example 1, except that a liquid electrolyte of 1.0 M concentration was injected into it, in which LiPF6 was dissolved in a non-aqueous organic solvent with a composition of ethylene carbonate (EC): ethyl methyl carbonate (EMC) = 30:70 (volume ratio), instead of the gel polymer electrolyte composition of Example 1, and only the impregnation process was performed.
[0184] <Comparative Example 3>
[0185] The lithium secondary battery was manufactured in the same manner as in Example 1, except that Li(Ni) was added as the positive electrode active material in a weight ratio of 96:1:3 to the positive electrode of Example 1. 0.8 Mn 0.1 Co 0.1 O2, carbon nanotubes as conductive materials, and PVDF as a binder.
[0186] <Comparative Example 4>
[0187] The lithium secondary battery was manufactured in the same manner as in Example 1, except that Li(Ni) was added as the positive electrode active material in a weight ratio of 93:3:1:3 to the positive electrode of Example 1. 0.8 Mn 0.1 Co 0.1 O2: Li as an inorganic solid electrolyte 1.4 Al 0.4 Ti 1.6 (PO4)3(LATP): Carbon nanotubes as conductive materials; PVDF as a binder.
[0188] <Experimental Example 1>
[0189] The positive electrodes prepared in Examples 1, 3, and 4 were cut through the center along the thickness direction, and SEM images of the cross-sections were taken and EDS analysis was performed.
[0190] At this point, the upper and lower layers in the thickness direction are analyzed separately, and the results are shown below. Figure 1 and Figure 2 And in Table 1 below.
[0191] [Table 1]
[0192]
[0193] Refer to the following Figures 1 to 2 Based on Table 1 above, it can be determined that the inorganic solid electrolyte is distributed in very similar amounts in both the upper and lower layers of the cathode mixture layer according to this disclosure.
[0194] <Experimental Example 2>
[0195] The lithium secondary batteries of Examples 1 to 3 and Comparative Examples 1 to 3 were fully charged at 25°C with a constant current of 0.33C until the voltage reached 4.2V. A heating pad made of mica was attached to such lithium secondary batteries, and the temperature was increased at 300W / min for 1 minute, and then maintained at 300W to create an external ignition environment. While maintaining these conditions, the voltage, pressure, and temperature of the lithium secondary batteries were measured over time, and the results are shown below. Figures 3 to 8 middle.
[0196] The difference between the maximum pressure measured when a lithium secondary battery explodes and the initial atmospheric pressure is defined as the explosion pressure, and the time from the point where the pressure begins to change to the maximum pressure is defined as the reaction time.
[0197] The lower the relative explosion pressure and the longer the reaction time, the lower the explosive power of the lithium secondary battery. The results are shown in Table 2 below.
[0198] [Table 2]
[0199]
[0200] Refer to the following Figures 3 to 8 Based on Table 2 above, it can be determined that the lithium secondary battery of the embodiment using LATP in the positive electrode and a gel electrolyte according to this disclosure exhibits the best values in terms of explosion pressure and reaction time, with an explosion pressure of 1.29 bar and a reaction time of 10.1 seconds. Comparative Example 1 shows an explosion pressure of 1.46 bar and a reaction time of 8.3 seconds. Therefore, compared with Comparative Example 1, the explosion pressure of Example 1 is reduced by 11.6%, and the reaction time is increased by 21.7%. When converted to explosion pressure / reaction time, it can be determined that Example 1 shows 0.128 bar / second, while Comparative Example 1 shows 0.176 bar / second, which shows a difference of 27.4%. Similarly, it can be determined that Comparative Example 2, which does not use a gel electrolyte, and Comparative Example 3, which does not use LATP in the positive electrode, also show similar results to those of Comparative Example 1.
[0201] <Experimental Example 3>
[0202] The lithium secondary batteries of Examples 1 and Comparative Examples 1 to 3 were charged at 25°C with CC-CV at 0.33C and 4.2V, and discharged at 0.33C with CC. The entire process was repeated 300 cycles, with the discharge capacity of the first cycle set to 100%, and the discharge capacity retention rate of the 300th cycle was calculated. The results are shown in Table 3 below. Figure 9 middle.
[0203] In addition, the DC resistance of the lithium secondary batteries of Examples 1 to 3 and Comparative Examples 1 to 4 was measured by the HPPC (Hybrid Pulse Power Characterization) method, and the results are shown in Table 3 below.
[0204] To measure the DC resistance, the lithium secondary battery was charged at 0.33C, 4.2V, and 0.05C cutoff using CC / CV, and discharged at 0.33C and 2.5V cutoff using CC, and the battery capacity was determined. Then, the fully charged lithium secondary battery was discharged to 50% capacity under the same charging conditions to set the SOC to 50%, and the DC resistance was measured at the corresponding SOC by discharging at 2.5C for 10 seconds.
[0205] [Table 3]
[0206]
[0207] Referring to Table 3, it can be determined that the resistance of Examples 1 and Comparative Example 2, in which LATP was added, appears to be relatively low. In this case, it can be determined that the resistance of the lithium secondary battery is reduced by approximately 2% to 3% compared to the case without LATP. However, it can be determined from Examples 1 and Comparative Example 4 that the resistance actually increases when the LATP content is 3% by weight. On the other hand, since the capacity retention is similar, it can be seen that the performance of other lithium secondary batteries according to this disclosure has not decreased.
[0208] Based on the above disclosure, those skilled in the art can make various applications and modifications without departing from the spirit and scope of this disclosure.
[0209] [Industrial Applicability]
[0210] In the lithium secondary battery according to this disclosure, the inorganic solid electrolyte is not only uniformly distributed within the positive electrode, but is also included in a predetermined amount or more. Therefore, the lithium secondary battery covers 50% or more of the surface of the positive electrode active material and further gels the electrolyte, thereby delaying the ignition of the lithium secondary battery, reducing the explosion pressure, increasing the reaction time, and reducing the explosive force. Thus, it can effectively improve the safety of the lithium secondary battery.
[0211] Furthermore, in the lithium secondary battery disclosed herein, the inorganic solid electrolyte can be uniformly distributed in the thickness direction even under high load, which is effective in ensuring the safety of the lithium secondary battery even under high load.
Claims
1. A lithium secondary battery, comprising: A positive electrode, wherein a positive electrode mixture layer comprising a positive electrode active material and an inorganic solid electrolyte is formed on one or both sides of the positive electrode current collector; A negative electrode, wherein a layer of negative electrode mixture containing negative electrode active material is formed on one or both sides of the negative electrode current collector; A separator inserted between the positive and negative electrodes; and Gel electrolytes, The inorganic solid electrolyte is included in an amount of 0.5% to 2% by weight based on the total weight of the positive electrode mixture layer, and is uniformly distributed within the positive electrode mixture layer.
2. The lithium secondary battery according to claim 1, When the positive electrode mixture layer is divided into two halves based on the thickness direction, the inorganic solid electrolyte is included in the upper layer in an amount of 40% to 60% by weight and in the lower layer in an amount of 40% to 60% by weight, based on the total weight of the inorganic solid electrolyte.
3. The lithium secondary battery according to claim 2, When the upper layer and the lower layer are each divided into two halves based on the thickness direction, the inorganic solid electrolyte is included in each layer in an amount of 20% to 30% by weight, based on the total weight of the inorganic solid electrolyte.
4. The lithium secondary battery according to claim 1, The total surface area of the positive electrode active material is covered by the inorganic solid electrolyte, which accounts for 50% to 90% of the total surface area.
5. The lithium secondary battery according to claim 1, The inorganic solid electrolyte is an oxide-based solid electrolyte with a NASICON structure.
6. The lithium secondary battery according to claim 1, The inorganic solid electrolyte is an oxide-based solid electrolyte represented by the following chemical formula 1: [Chemical Formula 1] Li 1+x M' 2-x M x (PO4)3 In chemical formula 1, 0<x<2, M' is selected from at least one of Ti, Zr, Ge, Sn, and Hf, and M is selected from at least one of Cr, Al, Mg, Ga, Sc, Y, In, and La.
7. The lithium secondary battery according to claim 6, The oxide-based solid electrolyte is a lithium aluminum titanium phosphate (LATP) compound in which M' is Ti and M is Al.
8. The lithium secondary battery according to claim 1, The loading of the positive electrode mixture layer is 400 mg / 25 cm. 2 Up to 600mg / 25cm 2 .
9. The lithium secondary battery according to claim 1, The gel-type electrolyte comprises: i) lithium salts, ii) non-aqueous organic solvents, and iii) At least one polymerizable compound selected from polymerizable monomers, oligomers, and copolymers having polymerizable unsaturated functional groups. At least a portion of the polymerizable unsaturated functional groups are cured.
10. The lithium secondary battery according to claim 9, The polymerizable unsaturated functional group is selected from at least one of vinyl, epoxy, allyl and (meth)acrylic groups.
11. The lithium secondary battery according to claim 9, The non-aqueous organic solvent mentioned above is a carbonate-based organic solvent.
12. The lithium secondary battery according to claim 9, The gel-type electrolyte further comprises a polymerization initiator, and the polymerization initiator is a photoinitiator or a thermal initiator.
13. The lithium secondary battery according to claim 12, The polymerization initiator is included in an amount of 0.01 to 20 parts by weight, based on 100 parts by weight of the polymerizable compound.
14. The lithium secondary battery according to claim 9, The gel electrolyte further comprises a functional additive, and the functional additive is selected from at least one of the following: sulfonyl lactone-based compounds, sulfite / ester-based compounds, sulfone-based compounds, sulfate / ester-based compounds, halogen-substituted carbonate-based compounds, nitrile-based compounds, cyclic carbonate-based compounds, phosphate / ester-based compounds, borate / ester-based compounds, and lithium salt-based compounds.